1991
DOI: 10.1111/j.1365-2621.1991.tb04719.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Characteristics of Three Formulations of Precooked, Vacuum‐packaged Restructured Beef Steaks

Abstract: Restructured steaks were manufactured with hot or cold boned beef using alginate, alginate + dried egg albumin, or salt/phosphate formulations. Raw steaks were sampled for aerobic (26" and 35"C), and gram-negative enteric counts. Cooked vacuum-packaged steaks were sampled for aerobic, gram-negative enteric, lactobacilli and staphylococci and for the presence of Salmonella, Aeromonas, Yersinia, and Listeria during 7 wk storage (2°C). No differences in counts due to formulation were found for raw or cooked steak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…Effects of cooking restructured emu steaks on microbial counts confirmed data of Payne et al (1991), who reported 16 EAPC/g in algin/calcium restructured beef steak after cooking to 60 °C. Wilkinson et al (1965) reported that Salmonella sp.…”
Section: Resultssupporting
confidence: 78%
“…Effects of cooking restructured emu steaks on microbial counts confirmed data of Payne et al (1991), who reported 16 EAPC/g in algin/calcium restructured beef steak after cooking to 60 °C. Wilkinson et al (1965) reported that Salmonella sp.…”
Section: Resultssupporting
confidence: 78%
“…The pH of fresh ground beef samples was 5.6 (Table 2), which was similar to what should be expected for fresh beef (Morris and others 1997; Shao and others 1999). As expected, pH values of samples were reduced ( P < 0.05) due to treatment with lactic acid, individually or in combination with Activa™RM or Fibrimex®, while combination of salt/phosphate and the algin/calcium meat binder with lactic acid affected the pH only slightly ( P > 0.05) (Means and others 1987; Payne and others 1991; Shand and others 1993). No significant ( P > 0.05) change in pH was observed during overnight storage for any of the treated samples or controls; however, pH values increased after cooking to 60 (rare) or 65 °C (medium‐rare).…”
Section: Resultssupporting
confidence: 63%
“…These increases, however, were significant ( P < 0.05) only for the Activa™RM + lactic acid and Fibrimex®+ lactic acid treatments. Several reports have documented increases in pH of restructured beef products when they were cooked (Trout and Schmidt 1984; Means and others 1987; Payne and others 1991).…”
Section: Resultsmentioning
confidence: 99%
“…ERKMEN cfu/g, these counts reached to lo9 to 10'" cfu/g in open air markets. S. aureus was isolated from vacuum-packaged beef steaks during storage at 2C (Payne et al 1991).…”
Section: Introductionmentioning
confidence: 99%